How a sticky fluid facilitates prey retention in a carnivorous pitcher plant (Nepenthes rafflesiana). (1st July 2021) - Kang, Victor; Isermann, Hauke; Sharma, Saksham; Wilson, D Ian; Federle, Walter
Abstract: Nepenthes pitcher plants grow in nutrient-poor soils and produce large pitfall traps to obtain additional nutrients from animal prey. Previous research has shown that the digestive secretion in N. rafflesiana is a sticky viscoelastic fluid that retains insects much more effectively than water, even after significant dilution. Although the retention of prey is known to depend on the fluid's physical properties, the details of how the fluid interacts with insect cuticle and how its sticky nature affects struggling insects are unclear. In this study, we investigated the mechanisms behind the efficient prey retention in N. rafflesiana pitcher fluid. By measuring the attractive forces on insect body parts moved in and out of test fluids, we show that it costs insects more energy to free themselves from pitcher fluid than from water. Moreover, both the maximum force and the energy required for retraction increased after the first contact with the pitcher fluid. We found that insects sink more easily into pitcher fluid than water and, accordingly, the surface tension of N. rafflesiana pitcher fluid was lower than that of water (60.2 vs. 72.3 mN/m). By analysing the pitcher fluid's wetting behaviour, we demonstrate that it strongly resists dewetting from all surfaces tested, leaving behind residual films and filaments that can facilitate re-wetting. This inhibition of dewetting may be a further consequence of the fluid's viscoelastic nature and likely represents a key mechanism underlying prey retention in Nepenthes pitcher plants. Statement of significance: Carnivorous Nepenthes pitcher plants secrete sticky viscoelastic fluids that prevent insects from escaping after falling into the pitcher. What physical mechanisms are responsible for the fluid's retentive function? First, insects sink and drown more readily in N. rafflesiana pitcher fluid due to its reduced surface tension. Second, once within the fluid, our force measurements show that it costs more energy to separate insects from pitcher fluid than from water. Third, the fluid strongly resists dewetting, making it harder for insects to extract themselves and covering their cuticle with residues that facilitate re-wetting. Such striking inhibition of dewetting may represent a previously unrecognised mechanism of prey retention by Nepenthes . Pitcher fluid fulfils a well-defined biological function and may serve as a model for studying the mechanics of complex fluids. Graphical abstract: Image, graphical abstract